Retention behavior of double-crown attachments with zirconia primary and secondary crowns - Schwindling, Franz Sebastian; Stober, Thomas; Schmitter, Marc; Rues, Stefan (Dental materials, 2016)
Objective - To investigate whether adequate retention of zirconia conical crown (CC) attachments can be achieved, and to investigate their long-term retention. - Methods - Sixteen individual zirconia primary crowns were produced with convergence angles of 1° or 2° (eight of each). After determination of the convergence angles of the primary crowns, monolithic zirconia secondary crowns were manufactured. To evaluate the retention behavior of all-zirconia CC, the crowns were fitted with forces from F=12.5-100N. Force magnitudes during the loosening process (L) were then measured. L/F ratios were recorded and the coefficient of friction (μ0) was calculated. Long-term retention was tested with up to 50,000 cycles of denture integration at a speed of 30mms−1 and a fitting force magnitude of 53N. - Results - Even when primary crowns were manufactured with the utmost care, the real convergence angles were greater than the nominal angles of the standardized burs (1° and 2°) by 0.28° (SD 0.11°). Without mechanical aging, mean L/F was 0.632 (SD 0.038) for 1° samples and 0.526 (SD 0.022) for 2° samples, indicative of high retentive forces of up to 63.2% of the fitting forces. When all the test results were used, best-fitting curves gave μ0=0.117 for new samples and μ0=0.126 for samples after 50,000 integration cycles. - Significance - When the correct milling and sintering parameters are chosen, the retention behavior of zirconia CCs is adequate and stable. This innovative type of attachment is appealing because of the beneficial properties of zirconia and the efficient CAD/CAM-based manufacture.
Gesehen am 21.10.2019